Stable angina diagnostics and treatment in elderly patients - V. P. Lupanov; D. M. Aronov (Кардиоваскулярная терапия и профилактика, 2008)
The review is devoted to diagnostics and differential treatment issues in elderly patients  with stable angina. Therapeutic potential of modern antianginal and other cardiovascular agents is presented. Clinical aspects of pharmaceutical therapy in coronary heart disease patients are emphasized. Surgery potential in elderly patients is also discussed.